Mechanisms of power generation during the take-off phase of dives are direction dependent - Mathiyakom, W.; McNitt-Gray, J. L.; Eagle, J.; Munkasy, B. (2000)
The results of the study suggest that differences in anatomical orientation coupled with translation direction may not influence absolute power generation but may influence the distribution of power generation between the ankle and the hip. This trade off between the ankle and hip has also been observed when landing gymnastics skills with different translation directions and anatomical orientations. the mechanical objective of translation and rotation of the body specific to each dive may impose directional constraint on lower extremity power generation mechanisms.